Lead Pollution Measurement Along National Highway and Motorway in Punjab, Pakistan - Hashim Farooq; Yasir Jamil; Muhammad Raza Ahmad; Muhammad Afzal Ahmad Khan; Tahir Mahmood; Zeeshan Mahmood; Zia-ul-Haq; Shakeel Ahmad Khan (Journal of Basic & Applied Sciences, 2012)
A study was conducted to determine qualitative and quantitative lead contamination in soil and vegetation along two major roadsides of Pakistan using Atomic Absorption Spectroscopy. There has been a rapid increase in vehicles on the highways using petroleum products, which has caused considerable raised the quantity of lead in the atmosphere increasing the risk to health. Laser Induced Breakdown Spectroscopy (LIBS) was used as multi elemental analysis technique to cross confirm the lead contamination in the samples. The samples of soil and grass were collected from each location 100m away from the edge of roads at every 25m. The levels of lead were found to be 125mg/kg to 87mg/kg respectively in soil and grass. Hence there is high accumulation of lead in roadside soil and vegetation of linking roads of highly populated cities of Pakistan, Faisalabad and Lahore.